2011
DOI: 10.1007/s13277-011-0274-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mast cells in benign odontogenic tumors

Abstract: The aim of this study was to investigate the presence of mast cells in a series of odontogenic tumors. Forty-five cases of odontogenic tumors were investigated using immunohistochemistry for mast cell triptase, and differences between groups were statistically evaluated. Mast cells were present in 96% of odontogenic tumors. Mast cells present in solid ameloblastoma were observed in the tumor stroma surrounding more solid and follicular epithelial islands, with or without squamous metaplasia. The odontogenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 49 publications
(65 reference statements)
3
34
0
2
Order By: Relevance
“…OM is a benign and aggressive tumor, with clinical behavior similar to ameloblastoma. Our finding in the case of OM is in agreement with the findings of Pereira et al [8] and Martínez-Mata et al [15], who did not report high MC densities in this lesion. Further studies on odontogenic tumors with mesenchymal and mixed origins can make the concept more clear.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…OM is a benign and aggressive tumor, with clinical behavior similar to ameloblastoma. Our finding in the case of OM is in agreement with the findings of Pereira et al [8] and Martínez-Mata et al [15], who did not report high MC densities in this lesion. Further studies on odontogenic tumors with mesenchymal and mixed origins can make the concept more clear.…”
Section: Discussionsupporting
confidence: 93%
“…In the mentioned studies, higher MC densities were observed in the subepithelial regions compared to the depths of connective tissues or progressive fronts of odontogenic cysts. However, Pereira et al [8] found higher densities of MCs in peritumoral areas compared to intratumoral regions. When a tumor becomes larger than 2 mm, angiogenesis must occur for further growth.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations